Hubungan Stress Dengan Kejadian Insomnia Pada Lansia Di UPTD PSLU Tresna Werdha Natar Lampung Selatan - Rahma Elliya; Prima Dian Furqoni; Mutiara Arini Ariska (Malahayati Nursing Journal, 2020)
ABSTRACT : CORRELATION OF STRESS WITH INSOMNIA AN ELDERLY AT UPTD PSLU TRESNA WERDHA NATAR SOUTH LAMPUNG Background : Based on population projection data, in 2017 there were about 23.66 million elderly in Indonesia (9.03%). It was predicted that the number of elderlies in 2020 (27.08 million), in 2025 (33.9 million), in 2030 (40.95 million) and in 2035 (48.19 million). The number of elderly in Lampung Province based on Health Office of Lampung Province in 2016 was 516.246, and the number of elderly in Bandar Lampung city according to Health office of Lampung Province in 2016 was 118.316 people. The number of elderly in UPTD PSLU Tresna Werda as many 85 people. Most of them are elderly who suffered from stress of insomnia. Stress suffered by elderly could influence the time to sleep. Purpose : To know the correlation of stress with insomnia on elderly at UPTD PSLU Tresna Werda Natar South Lampung Year of 2019.Methods : This research type is Quantitative. The research design was Analytical Survey design method with cross sectional approach. The population as many 80 respondents, with 54 respondents, sampling in research was purposive sampling. Statistical test was by using chi square test.Result : There was the correlation of stress with insomnia on elderly at UPTD PSLU Tresna Werda Natar South Lampung Year of 2019 (p value 0.010. OR 5.6).Conclusion: There was the correlation of stress with insomnia on elderly at UPTD PSLU Tresna Werda Natar South Lampung Year of 2019.  Keywords: stress, insomnia, elderly  INTISARI : HUBUNGAN STRESS DENGAN KEJADIAN INSOMNIA DI UPTD PSLU TRESNA WERDHA NATAR LAMPUNG SELATAN Pendahuluan : Saat ini banyak masalah yang terjadi pada lansia baik secara fisik maupun psikologis, salah satunya adalah insomnia.Stres yang dialami oleh lansia dapatmempengaruhi kebutuhan waktu untuktidur.Jumlah lansia di UPTD PSLU Tresna Werda sebanyak 85 orang. Hasil presurvey menunjukkan sebanyak 70% mengalami kesulitan tidur.Tujuan : Diketahui hubungan stress dengan kejadian insomnia pada lansia di UPTD PSLU Tresna Werda Natar Lampung Selatan Tahun 2019.Metode : Jenis penelitian ini adalah Kuantitatif. Desain penelitian metode desainSurvei Analitik dengan pendekatan cross sectional Populasi sebanyak 80 responden, dengan sampel sejumlah 54 responden, pengambilan sampel pada penelitian purposive sampling Uji statistik menggunakan uji chi square.Hasil penelitian: Adahubungan stress dengan kejadian insomnia pada lansia di UPTD PSLU Tresna Werda Natar Lampung Selatan Tahun 2019 (p value 0,010. OR 5,6).Kesimpulan: Adahubungan stress dengan kejadian insomnia pada lansia di UPTD PSLU Tresna Werda Natar Lampung Selatan Tahun 2019. Lansia mengalami stres dikarenakan tidak adanya dukungan keluarga dan kurangnya aktivitas fisik.  Kata Kunci          : Stress, Insomnia, Lansia